Rancang Bangun Alat Penghitung Curah Hujan Tipe Tipping Bucket Berbasis Arduino Uno ATmega328p - Renaldy, Renaldy; Syahrir, Syahrir; Natalisanto, Adrianus Inu (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2023)
Rainfall from one area to another varies and can occur at any time. This requires a tool that can monitor the rainfall that occurs. One of the automatic rainfall gauges tipping bucket. This tool will be designed based on Arduino Uno ATmega328P and the results will be compared with manual measuring tools. This study uses a quantitative approach and primary data by designing and manufacturing a rainfall sensor tool the tool is applied to obtain rainfall data which will later be compared with manual rainfall data. Light rainfall simulation measurement data has the highest rainfall value of 10.770 mm. For rainfall simulation measurement data of 26.924 mm and heavy rainfall simulation measurement data of 64.618 mm. Comparison of type rainfall measurement data tipping bucket and manual measuring tools are not much different from the rainfall calculator tipping bucket quite accurate. The design of a tipping bucket type rainfall meter by utilizing the Arduino Uno microcontroller connected to the RTC, I2C LCD and sensor reed switch which reads the movement of the tipping bucket so that the sensor works by detecting a magnet that hits the front of the sensor whose results will be displayed on the LCD. The level of accuracy of the tool is quite accurate and rainfall is directly proportional to time.